Client influence on valuer behaviour in South Africa - nature, prevalence and consequences - Wilkens, Lyle Jan (Department of Construction Economics and Management, 2015)
The primary purpose of this study is to investigate the presence of client's influences on property valuer behaviour in South Africa. The study aims to investigate the existence of these influences, the variables of these influences and the possible consequences for the valuation industry. International literature reveals that this phenomenon is prevalent in a number of countries. This study aims to uncover this phenomenon in South Africa. Registered South African valuers are targeted by survey questionnaires to extract the relevant data necessary to support this claim. The response rate is a broad representation and sufficient data is gathered for the research purposes. Furthermore, prominent valuation companies and valuers are interviewed in order to elaborate and support the data extracted from the survey questionnaire. The study indicates that client influence on valuers exists in South Africa and that a majority (54%) of practising valuers have adjusted their valuations after client interaction. The concern is that this prevalence of influence will be detrimental to the valuation industry in South Africa. This study aims to promote awareness of these influences, and recommendations are made to curb this phenomenon.